ANALISIS CONSUMER BEHAVIOUR DALAM PEMBELIAN WINES DI PERUSAHAAN IFOOD - Sinaga, Angel Mauledya; Arianto, Dede Brahma (PT Naureen Digital Education, 2023)
This study aims to determine consumer behavior in buying wine at the iFood company. Ifood is a Brazilian company that has a large market share in selling wine. The data used in this study is a secondary type of data derived from iFood Marketing Analytics available on Kaggle. Data processing using Google Colab and the methods applied are Exploratory Data Analysis (EDA) and Correlation Analysis. Based on the correlation analysis, it was found that the variables that correlated highly with the level of wine sales (MntWines) were the variables of income level (Income), meat purchase rate (MntMeatProducts), purchases using catalogs (NumCatalogPurchases), direct purchases in stores (NumStorePurchases), and the number of total purchases at iFood companies (MntTotal).